Body Image in Relation with Stress Level and Self-Esteem Among Adolescents with Thalassemia Major - Felicia Kurniawan; Magdalena Surjaningsih Halim; Surilena Surilena; Elisabeth Eileen Santoso; Sarah Agatha Indra; Valencia Valencia (Faculty of Medicine Universitas Padjadjaran, 2026)
Background: Body image influences how adolescents perceive and accept physical changes. Adolescents with thalassemia major require regular blood transfusions, which may lead to iron overload and complications such as bone and skull deformities, growth delay, and low body mass index. These physical changes may contribute to body dissatisfaction, stress, and reduced self-esteem. This study aimed to examine the relationship between body image, stress, and self-esteem among adolescents with thalassemia major.Methods: This analytical observational study used a cross-sectional design and was conducted from July to October 2023. A total of 54 adolescents aged 12–19 years from Jakarta, Bekasi, and Bogor participated in the study. After obtaining informed consent from their mothers, participants completed the Multidimensional Body-Self Relations Questionnaire–Appearance Scales (MBSRQ-AS), the Depression Anxiety Stress Scales (DASS-42), and the Rosenberg Self-Esteem Scale (RSES). Body image, stress level, and self-esteem were assessed using these instruments. Data were analyzed using the chi-square test.Results: Most participants were female (61.1%), with a mean age of 14.4 ± 2.42 years. The majority had a positive body image (61.1%), were not experiencing stress (70.4%), and had high self-esteem (83.3%). No significant associations were found between body image and stress (p=0.630), body image and self-esteem (p=0.261), or stress and self-esteem (p=0.274).Conclusion: No significant associations were observed between body image and stress, body image and self-esteem, or stress and self-esteem among adolescents with thalassemia major. Despite disease-related physical changes, most participants reported a positive body image, low stress levels, and high self-esteem.